Creativity, Pluralism, and Fictitious Narratives: Understanding IP Law Through Karl Polanyi - Suthersanen, Uma (2022)
For over a century, jurists have debated as to whether IP rights should be extended to this or that output such as photographs, computer programs, products of data aggregation, virtual objects, natural and organic materials, “creative” algorithms, and genes. What is surprising is the continuing and bifurcating discourse landscape: “IP law protects and rewards creativity” versus “IP law protects investment”. This paper suggests that IP law indiscriminately and simultaneously protected all sorts of res emanating from creative and entrepreneurial labour as well as from capital investment. Continued attempts to discuss or adjudicate IP law, policy and reform through strict conceptual silos such as creativity, labour, and investment are doomed narratives.Instead, I invite readers to appreciate that early modern rules in sensu lato were about mixed motivations of reward, investment, recognition, competition, honour, public interest, and more. The implicit suggestion in this paper is that the root cause of continuing legal conundrums today is the failure to appreciate the pattern set out by two related socio-legal mappings: (i) motivations for early rules in relation to creative and entrepreneurial labour and products in Europe; and (ii) the extent to which current IP norms and laws evolved to absorb such myriad motivations over five hundred years. I employ Karl Polanyi’s theory on the commodification of labour, including investment-backed labour, into tradeable, fictitious commodities, where law and property are recognised as vital institutional tools which disembed and re-embed society from/into the economy. Polanyi’s motivation ethos is effective in synthesising the different mapping points to create a pointilliste landscape which, in turn, shows why IP law only makes juridical sense if it is viewed as a pluralistic concept.
Keywords: creativity; intellectual property; pluralism

Platform Power and Regulatory Politics: Polanyi for the 21st Century - Cioffi, John W.; Kenney, Martin; Zysman, John (2021)
The rapid rise, expansion, and growing asymmetric power of online platform firms towards other businesses, labor and even the state itself occurred in a context of minimal regulatory oversight. In many respects, because the existing legal system was handicapped in understanding and regulating the new platform business models. The platform firms undermined traditional industry boundaries and developed surprising synergies by expanding in unexpected ways due to their ability leverage data and computational expertise. The growth of these platforms was accompanied by minimal intervention by state actors until recently, as concerns about the platform firms’ remarkable power has attracted the concern of States globally and the previous regime is giving way to intense debate and increasingly interventionist governmental policies and enforcement actions. We examine several salient aspects of this emerging regulatory and political reaction, and suggest that this represents an attempt to rebalance the positions of social groups in their relationship to the increasingly central platform firms. First, we view the rise of, and recent political responses to, the often-predatory power and manipulative conduct of platform firm in terms of a “Polanyian” double movement in which the destabilizing and destructive effects of unchecked corporate power and market development eventually generates political and regulatory responses to constrain private actions by new economic actors as they threaten the social, political, and economic order. Second, incipient legal changes, most notably the EU’s proposed Digital Markets Act and Digital Services Act, indicate a shift in regulatory emphasis from competition (and antitrust) policy and law, which has proven limited in its capacity to address inherent monopolistic tendencies of platform firms and markets, towards more intensive and encompassing forms of social and economic regulation. Finally, the political dynamics of legal and institutional change open up new possibilities for political economic and societal reordering, but the particular changes will likely vary in character and significance across political jurisdictions, and therefore follow distinctive and possibly divergent developmental trajectories. We hypothesize that the EU may be able to become the first-mover in regulating the powerful multinational platform firms. We recognize that we are at the very beginning of a transformational process that is likely to reorder old and generate new political economic interests, identities, coalitions, and conflicts at the sectoral, national, regional, and international levels.
Keywords: European Union; Platform economy; Polanyi; antitrust; monopoly

Pandemic Paradox and Polanyi: Financial Markets Rise, Economies Crash, and Regulators Toss a Coin - Findlay, Mark (2020)
In the pandemic, investors like all responsible citizens share an obligation to keep the community safe. This obligation extends to informed market decision-making which goes beyond self-interest. The current disconnect between financial markets and the economy is a story of two different realities – or perhaps one harsh reality and one expectant gamble. The disconnect cannot just be explained by the different purposes of economic and financial market analysis but rather by the information indicators on which these rely. To forewarn regulators concerned that these two worlds of global wealth generation and growth moving to polar opposite futures, this brief review has these aims:• To reflect on a legal model for financial markets, their regulation and its limitations so that law and finance may be understood as positively relational when considering market sustainability; and then• To suggest that the explanation for this dangerous disconnect can be found in Karl Polanyi’s understanding of fictitious commodities in self-regulating markets, dis-embedding from the social and his propositions for market correction through the double movement.Despite the neoliberal logic to the contrary (where financial markets are deemed only for maximising investor/shareholder profit) financial market regulation should prioritise market sustainability as part of pandemic control policy.
Keywords: disconnect; economy; financial markets; market sustainability and resilience; pandemic crisis; responsible market decision-making

Transformation or Structural Change? What Polanyi Can Teach Us about the Platform Economy - Kenney, Martin; Zysman, John; Bearson, Dafna (2020)
The rise of the platform economy marks the latest phase in the ongoing digital revolution. Indeed, the platform is to this digital era what the factory was to the industrial era, both a symbol and an organizing mechanism. Gernot Grabher and Jonas König (2020) used Karl Polanyi’s analysis of what he termed the “great transformation” to frame the rise of platform economy. The platform economy is remarkable as it confirms Polanyi’s (and Marx’s before him) insight that the reach of the market is based upon increased commodification as it has been able to reach into ever more parts of social life. We introduced the term “platform economy” in 2015 because we recognized that the digital platforms were changing the dynamics of capitalist accumulation —- an analysis framed by regulationist school of political economy. The intuition was that the socio-technical innovation of digital online platforms was the critical fulcrum for an economic restructuring that would rewire the flows of data and ultimately money and power. The firms we have termed the “mega-platforms”, Apple, Amazon, Facebook, Google, and Microsoft, have become the most valuable and powerful firms in the world. Importantly, the reach of these platforms is global and yet local and personal. Moreover, this platform power has only been reinforced during the COVID-19 pandemic.
Keywords: COVID-19; Great Transformation; Polanyi; platform economy